Improvement of dyes degradation using hydrofluoric acid modified biochar as persulfate activator. Issue 1 (1st January 2019) - Li, Feiyue; Xie, Yue; Wang, Yan; Fan, Xingjun; Cai, Yongbin; Mei, Yanyan
ABSTRACT: The hydrofluoric acid modified biochar (HF-BC) was obtained, aiming to improve its performance for activating persulfate (PS) to make acid orange 7 (AO7) degraded in water solution. Results showed that the surface area, micropore volume, carboxyl and phenolic hydroxyl group content of HF-BC increased by 171%, 172%, 23.8% and 50%, respectively, compared to unmodified biochar (BC). The decolorization of AO7 in HF-BC/PS and BC/PS systemwas much more rapid and efficient than that in HF-BC, BC and PS alone system. For the HF-BC/PS system, the AO7 was removal of 99.8%, much higher than that of BC/PS system, probably because of its better surface characteristics. Moreover, for the HF-BC/PS system, it was the higher PS concentration and HF-BC dosage that caused greater AO7 degradation rates, and lower pH was favorable for the degradation. Our results provided a novel method to design biochar as an activator for persulfate-based remediation of dye wastewater. Abbreviations: HF-BC, hydrofluoric acid modified biochar; BC, unmodified biochar; AO7, Acid orange 7; PS, persulfate